Influence of pores on the corrosion and cracking of the reinforced concrete suffered by the chloride ions and stray current - Wenjun Zhu; Xinyun Yang; Fan Tang; Fei Dong (European Journal of Environmental and Civil Engineering, 2026)

Targeted regulation and extraction mechanism of rare earth elements and thorium during the decomposition of rare earth concentrates - Xiaowei Zhang; Likai Zang; Feng Guo; Yanhong Hu; Jinxiu Wu; Wenjun Fan; Jianguo Cui; Na Li; Xiaodong Wang; Ruifeng Ma (Minerals Engineering, 2026)

Thermal mechanisms reorganize, not merely attenuate, across the urban–rural gradient: A diurnal analysis of land surface temperature drivers in Changsha, China - Qianjun Wei; Dongxuan Zhou; Xinying Yang; Wenzhong Zhang; Siyu Fan; Wenjun Kuang; Shuchang Luo; De Yu; Jie Tan (Sustainable Cities and Society, 2026)

Efficient photoelectrocatalysis for dibutyl phthalate degradation and simultaneous hydrogen evolution using an S-scheme F-BiOF/TiO2 nanocones heterojunction - Zhenzhen Fan; Jianheng Xin; Jinfeng Zhi; Yunpeng Wang; Wenjun Yan; Yujing Guo; Zhongping Li; Lifang Fan (Journal of Environmental Chemical Engineering, 2026)

Innovative V-shaped buckle-based in-situ joint reinforcement technology for the transmission tower: Mechanistic synergy and quantitative tensile capacity enhancement - Chongkai Fan; Yixin Xie; Lixiang Ye; Wenjun Tang; Dachang Zhang (Engineering Structures, 2026)

A versatile near-infrared fluorescent probe for Zn2+ detection in food and biological matrices - Tianjiao Hou; Chunlin Fan; Hong Deng; Yifei Sun; Wenjun Miao; Chunyuan Hou; Yu Zhang; Jun Luo; Xuan Shen (Analytica Chimica Acta, 2026)

Effects of impurities on the rheological behavior of rare earth concentrate slurry and the regulatory role of retarders - Xiaodong Wang; Xiaowei Zhang; Feng Guo; Yanhong Hu; Jinxiu Wu; Wenjun Fan; Likai Zang; Qifu Yuli; Zhao Yu; Ruifeng Ma (Minerals Engineering, 2026)

Lignin-based aqueous epoxy emulsified asphalt: Preparation, performance characterization, and sustainable applications - Fenglei Zhang; Li'er Chen; Shi Fan; Wenjun Huang; Bobo Zhang; Yuyang Ao; Xin Jin; Yan Sun; Hongzhou Zhu (Journal of Cleaner Production, 2026)

Combined toxicity and mechanism of cadmium and neonicotinoid insecticide to rice (Oryza sativa L.): reduced antioxidant defence mediated by flavonoid - Zhaoxia Fan; Na Liu; Fei Ge; Feng Li; Wenjun Zhou; Juan Gao (ENGINEERING Environment, 2026)

Spectral and structural analysis of a new lactone metabolite isolated from a mangrove endophytic fungus - Meijing Tan; Shichao Ju; Fan He; Wenjun Li; Youquan Wei; Rui Pi; Xishan Huang; Yanjun Zhang (Natural Product Research, 2026)

Guxiaspergiltones A-J: Furanone-type polyketides with anti-inflammatory activities from the mangrove endophytic fungus Aspergillus sp. GXNUW29 - Fan He; Furong Wu; Meijing Tan; Xianglong Bo; Shichao Ju; Wenjun Li; Youquan Wei; Jiao Wu; Xishan Huang (Phytochemistry, 2026)

Dynamic changes and functional analysis of the vaginal microbial communities in reproductively dysfunctional giant pandas - Xin Chen; Ling Dao; Wenjun Huang; Bi Li; Xiaolan Wang; Zhengyu Chen; Fangfang Liu; Li Luo; Fan Xu (The Veterinary Journal, 2026)

Antioxidant Enzyme Activities and Metabolic Responses of the Posterior Gills of Mud Crab (Scylla paramamosain) Under Long-Term Stress in Coastal Chloride-Dominated Low-Salt Saline-Alkali Water - Ziwei Fan; Kangxiang Qin; Fei Wang; Chenxi Che; Yuntao Li; Wenjun Li; Shan Gao; Chunlin Wang; Changkao Mu; Huan Wang (Journal of Ocean University of China, 2026)

A new diphenyl ether with insecticidal activity from the mangrove endophytic fungus Aspergillus sp. GXNU-DY2-12 - Meijing Tan; Shichao Ju; Fan He; Wenjun Li; Youquan Wei; Weifeng Xu; Ruiyun Yang; Xishan Huang (Natural Product Research, 2026)

Probabilistic stratigraphic modeling of waste soil landfills using multiple UAV data - Shuairong Wang; Shuai Zhang; Haoquan Wang; Hui Wang; Fan Zhang; Ping Shen; Wei Yan; Wenjun Zhang; Zhuofeng Li; Liangtong Zhan (Computers and Geotechnics, 2026)

Development and Application of a Method to Enhance Lipase Performance and Wastewater Treatment Capacity Using DES - Jiaxin Song; Chuanlong Yu; Fangling Wu; Li Yuan; Danna Fan; Yiheng Zhang; Yuping You; Guoqiang Wu; Zedong Zhang; Wenjun Wang (Sugar Tech, 2026)

Two new polyketide derivatives isolated from the mangrove-derived fungus Aspergillus sp. GXNU 2Y10 - Fan He; Wenjun Li; Youquan Wei; Jiao Wu; Congli Lei; Zhenlan Li; Zheng Xiong; Xishan Huang (Natural Product Research, 2026)

High-level chloramphenicol degradation in mariculture wastewater via cathodic nitro-reduction in a single-chamber bioelectrochemical system - Haoran Xin; Sihao Chen; Xin Li; Zhongying Chen; Qingjuan Fan; Haiping Luo; Guangli Liu; Wenjun Mai (Water Research, 2026)

Mediating role of the maternal placental growth factor levels on association between ozone exposure and adverse pregnancy outcomes - Yajuan Wang; Yuanyuan Yu; Yang Li; Xiaoli Gao; Wenjun Fan; Xuening Bai; Xiaozhou Li; Jiayan Zhou; Ying Zhang; Qisijing Liu; Chen Li; Rongrong Wu; et al. (Environmental Research, 2026)

A sequentially activatable DNAzyme nanosystem for augmented tumor gene silencing and radiosensitization - Han Wu; Xianzhou Cai; Hao Jiang; Qin Fan; Jifeng Li; Wenjun Zhu; Longyu Zhao; Yingjie Ren; Ziliang Dong; Lianhui Wang (Chemical Engineering Journal, 2026)

Effects of high-pH saline-alkaline water on tissue structure, osmoregulation, antioxidant capacity, and metabolic activity in mud crab Scylla paramamosain Estampador, 1950 - Yuntao Li; Cunhong Chen; Zihui Li; Jingli Yang; Chenxi Che; Shan Gao; Kangxiang Qin; Peng Yang; Ziwei Fan; Wenjun Li; Chunlin Wang; Changkao Mu; et al. (Aquaculture, 2026)

Multi-Scale Pore System and Its Implication for Shale Oil Occurrence in Alkaline Lacustrine Mixed Sedimentary Shale Reservoirs: A Case Study from Fengcheng Formation, Mahu Sag, Junggar Basin - Yuanhao Zhang; Zhenxue Jiang; Jiaqi Chang; Zhiye Gao; Liliang Huang; Wenjun He; Chengju Zhang; Lei Chen; Qingqing Fan; Yunhao Han; Bolin Zhang; Chao Chen (Journal of Earth Science, 2026)

Two new polyketone derivatives from the mangrove endophytic fungus Aspergillus sp. GXNU TH4b - Shichao Ju; Xianglong Bo; Furong Wu; Meijing Tan; Zisuo Song; Fan He; Wenjun Li; Youquan Wei; Weifeng Xu; Ruiyun Yang; Xishan Huang (Natural Product Research, 2026)

SIRT3/AARS2 regulates SOD2 lactylation to determine neuronal fate in TBI - Jiazhi Song; Jing Liu; Wenjun Fan; Fang Gou; Hong Yang; Ping Wang; XiaoKun Yang; Kai Tao (Molecular Neurobiology, 2026)

Sunlight and suicide risk: mediating effect of high temperature in China - Xiuya Xing; Yiming Gai; Qin He; Wenjun Cheng; Jingli Zhu; Qianyao Cheng; Yinguang Fan; Hong Su; Huadong Wang; Zhongliang Bai; Jian Cheng (International Journal of Biometeorology, 2026)

Shift work and metabolic dysfunction-associated steatotic liver disease: a systematic review of observational studies - Bingya Ma; Yihang Fan; Wenjun Fan (International Archives of Occupational and Environmental Health, 2025)
Objective Shift work disrupts the circadian rhythm and may increase the risk of metabolic disorders, including nonalcoholic fatty liver disease, recently redefined as metabolic dysfunction-associated steatotic liver disease (MASLD), and its progressive form, metabolic dysfunction-associated steatohepatitis. This systematic review aimed to synthesize observational studies on the association between shift work and MASLD. Methods A comprehensive literature search was conducted in the PubMed, Scopus, and Web of Science databases up to November 25, 2024, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Data were extracted and summarized based on pre-specified inclusion and exclusion criteria. The National Institutes of Health quality assessment tool was used to evaluate the quality of the included studies. Both data extraction and quality assessment were conducted independently by two authors, with disagreements resolved through consensus. Results Nine studies met the criteria and were included in the review, including various occupational groups. Most studies reported a positive association between shift work and MASLD, with stronger effects observed in workers exposed to long-term or frequent shift work. Subgroup and interaction analyses suggested that gender, age, lifestyle, chronotype, and occupational factors may modify this association, while body mass index was identified as a potential mediator of the relationship between shift work and MASLD. However, methodological issues, such as imprecise exposure and outcome measurements and a lack of time-varying analysis, limit causal interpretation. Conclusion The systematic review supports an association between shift work and increased MASLD risk. Further prospective studies with rigorous designs and diverse populations, as well as stronger mechanistic evidence, are needed to establish a causal link between shift work and MASLD.

Investigation of the Alterations in the Gut Microbiota and Intestinal Mucosa in Mice Infected with Echinococcus multilocularis - Deping Cao; Wenjun Huang; Mingquan Pang; Jiajing Li; Haitao Huang; Hui Ma; Dayu Li; Yufei Qin; Xiaohong Peng; Haining Fan (Acta Parasitologica, 2025)

A High-Resolution Mirror Migration Framework for Ocean Bottom Cable Seismic Data - Wenjun Ni; Shaoyong Liu; Mingyuan Xu; Bingkai Han; Guodong Fan (Journal of Marine Science and Engineering, 2025)
Seismic data migration is a critical step for accurate subsurface imaging. While Ocean Bottom Cable (OBC) surveys provide high-quality seismic data, reliance on primary reflections alone leads to significant illumination gaps. Receiver-side ghost waves can mitigate these gaps; however, conventional mirror migration suffers from low resolution and amplitude inaccuracy. To address these limitations, this study introduces a high-resolution mirror migration framework based on Point Spread Function (PSF)-guided inversion imaging. The methodology involves first separating the OBC wavefield to isolate ghost-wave components, followed by applying standard mirror migration to produce an initial, blurred image. Subsequently, the PSFs of down-going ghost waves are estimated to characterize imaging distortions, and image-domain least squares migration (LSM) is implemented via PSF deconvolution to reconstruct high-resolution reflectivity. Numerical experiments on complex models demonstrate that the proposed method preserves the additional illumination provided by this wavefield, substantially improves the spatial resolution of imaging targets, and enhances lateral continuity. Quantitative analysis confirms this enhancement through a significant extension of the effective vertical wavenumber bandwidth and the recovery of higher-frequency content. The framework provides a robust and computationally efficient solution for high-fidelity OBC imaging, enabling more reliable subsurface interpretation.

Soil aggregates stability is evidently enhanced by super-binding of the N-terminal disordered tail of glomalin to soil minerals - Minghui Jia; Youchao Wang; Jin He; Shan-Ho Chou; Dehua Luo; Linchuan Fang; Jingtao Hou; Yuke Fan; Wenjun Zhang; Hansong Chen; Dejian Zhou; Yurong Liu; et al. (Soil Biology and Biochemistry, 2025)

Maternal placental growth factor mediates the association between PM2.5 and its constituents with adverse pregnancy outcomes - Yuanyuan Yu; Wenjun Fan; Jiayan Ni; Xiaoli Gao; Weixia Li; Jianqiong Zheng; Hongping Zhang; Juan Chen; Qisijing Liu; Zi Lin; Bin Chen; Yajuan Wang; et al. (Journal of Hazardous Materials, 2025)

Theoretical analysis and process research on recycling ITO waste targets by carbon thermal reduction method - Jianjun Yang; Ganwei Lei; Caihe Fan; Yuhao Lan; Yang Yang; Weiping Liu; Zhenghua Zhou; Wenjun Ling; Zhimei Xia; Tao Tao; Zhiwu Ouyang; Guihai Zhang; et al. (Journal of Environmental Chemical Engineering, 2025)

A review of curcumin-mediated photodynamic bactericidal technology for food preservation: Limitations and improvement strategies - Zhenlong Zhou; Pengzhen Li; Ruoxin Chen; Xinyu Cai; Wenjun Zhang; Penghui Fan; Jianyu Su (Food Microbiology, 2025)

Mining marine dinoflagellate Amphidinium carterae for peridinin production by optimizing light conditions and mixotrophy strategy - Zhiwei Hong; Sheng Qiu; Jiawei E; Wenjun Zhang; Yuchen Yuan; Liyun Sun; Jianhua Fan (Bioresource Technology, 2025)

Soil organic matter enhances urease-mediated microbially induced carbonate precipitation: Dual benefits for inorganic carbon sequestration and cadmium immobilization - Chonghao Jia; Yuke Fan; Qiangqiang Wei; Lijun Wang; Wenjun Zhang (Journal of Hazardous Materials, 2025)

Discrimination of tea varieties and bud sprouting phenology using UAV-based RGB and multispectral images - Litao Sun; Jiazhi Shen; Yilin Mao; Xiaojiang Li; Kai Fan; Wenjun Qian; Yu Wang; Caihong Bi; Hui Wang; Yang Xu; Jingbiao Xu; Zhaotang Ding (International Journal of Remote Sensing, 2025)

Quinoa greens as a novel plant food: a review of its nutritional composition, functional activities, and food applications - Huange Huang; Qiang Wang; Jianxin Tan; Chunxiang Zeng; Junying Wang; Jingwei Huang; Yichen Hu; Qi Wu; Xiaoyong Wu; Changying Liu; Xueling Ye; Yu Fan; et al. (Critical Reviews in Food Science and Nutrition, 2025)

Sex-dependent effects of heat exposure on the middle ear health in mice - Jie Li; Wenjun Fan; Xiangyi Yuan; Teng Wan; Li Qin; Lu Zhang; Tong Hou; Cuiqing Liu; Ran Li (Journal of Thermal Biology, 2025)

Insights into the interlinkages between rhizosphere soil extracellular enzymes and microbiome assemblages across soil profiles in grasslands - Xueqing Liu; Xifeng Fan; Mingcai Zhang; Hui Zhang; Yuesen Yue; Juying Wu; Wenjun Teng; Na Mu; Ke Teng; Haifeng Wen (Applied Soil Ecology, 2025)

Intergeneric protoplast fusion for probiotic strain improvement: Molecular mechanisms and metabolic analysis - Haiting Duan; Xin Su; Qiqi Fan; Haochen Zhang; Bilige Menghe; Wenjun Liu (Food Bioscience, 2025)

A potent dual inhibitor targeting COX-2 and HDAC of acute myeloid leukemia cells - Xiang Qin; Xueting Wang; Chunmei Yang; Fan Wang; Tingting Fang; Didi Gu; Qulian Guo; Qiuyu Meng; Wenjun Liu; Lu Yang (Molecular Diversity, 2025)

Cytotoxic metabolites from the mangrove endophytic fungus Aspergillus sp. GXNU QG1a - Xianglong Bo; Yufei Zhao; Feng Qin; Furong Wu; Meijing Tan; Shichao Ju; Zishuo Song; Wenjun Li; Fan He; Youquan Wei; Hua Xu; Xishan Huang (Natural Product Research, 2025)

Effect of compound exposure to snowstorm and cold spell on acute myocardial infarction mortality - Jihong Hu; Zhiwei Li; Jingli Zhu; Qin He; Wenjun Cheng; Qianyao Cheng; Yinguang Fan; Hong Su; Huadong Wang; Zhongliang Bai; Xiuya Xing; Jian Cheng (Environmental Research, 2025)

Associations of welding-related metals and hypertension in male welders: Roles of cytokinesis-block micronucleus cytome assay parameters - Xiayun Dai; Fan Wang; Yonggang Liao; Na Tu; Xiaolei Fu; Wenjuan Fu; Yizhe Sun; Junpin Liu; Siyu Wan; Wenjun Yin; Wei Pi; Jiaojun Liang; et al. (Environmental Pollution, 2025)

Metformin-induced precise targeted inhibition of ischemic neuronal death by a programable endogenous ROS-responsive nanoprodrug - Xiaofeng Tan; Ying Li; Hao Jin; Yu Zhou; Wenjun Li; Yun Zhao; Jun Hai; Jinyao Li; Zhongxiong Fan; Lichao Yang (Chemical Engineering Journal, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Tensile Fracture Behaviour of Stratified Sandstone Under Static and Dynamic Loading - Wenbing Fan; Junwen Zhang; Jiawei Liu; Kailun Fang; Wenjun Li; Shaokang Wu; Yang Zhang; Xukai Dong (Rock Mechanics and Rock Engineering, 2025)

Synthesis of porous CNS@C@NC concave cubic nanobox composite as cathode material for aluminum batteries - Wenbin Luo; Jian Li; Yi Yu; Wenwei Su; Zetong Ren; Bo Niu; Zisheng Chao; JinCheng Fan; Wenjun Yi (Chemical Engineering Journal, 2025)

Effect of low temperature on myocardial infarction mortality in rural residents: comparison of daytime and nighttime exposure - Xiuya Xing; Wenjun Cheng; Qin He; Yiming Gai; Jingli Zhu; Qianyao Cheng; Yinguang Fan; Hong Su; Zhongliang Bai; Huadong Wang; Jian Cheng (International Journal of Biometeorology, 2025)

Corrigendum to “Effects of aquatic Ca2+ and Mg2+ on the antioxidant, immune, osmotic regulation, molting, and metabolic abilities of Scylla paramamosain” [Aquaculture, Volume 586, Part 2, 15 February 2025, 741875] - Yuntao Li; Chenxi Che; Shan Gao; Kangxiang Qin; Peng Yang; Ziwei Fan; Wenjun Li; Chunlin Wang; Changkao Mu; Huan Wang (Aquaculture, 2025)

Inhibition of soluble epoxide hydrolase ameliorates cerebral blood flow autoregulation and cognition in alzheimer's disease and diabetes-related dementia rat models - Chengyun Tang; Jane J. Border; Huawei Zhang; Andrew Gregory; Shan Bai; Xing Fang; Yedan Liu; Shaoxun Wang; Sung Hee Hwang; Wenjun Gao; Gilbert C. Morgan; Jhania Smith; et al. (GeroScience, 2025)

Effects of aquatic Ca2+ and Mg2+ on the antioxidant, immune, osmotic regulation, molting, and metabolic abilities of Scylla paramamosain - Yuntao Li; Chenxi Che; Shan Gao; Kangxiang Qin; Peng Yang; Ziwei Fan; Wenjun Li; Chunlin Wang; Changkao Mu; Huan Wang (Aquaculture, 2025)

In vitro induction and characterization of octaploid Schizachyrium scoparium, an ornamental grass - Zhuolin Xiao; Mingjun Wei; Yue Xu; Haochen Nie; Hui Zhang; Ke Teng; Wenjun Teng; Juying Wu; Xifeng Fan; Yuesen Yue (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Prevalence and Molecular Characterization of Cryptosporidium spp., Giardia duodenalis and Enterocytozoon bieneusi in Donkeys of Inner Mongolia, Northern China - Li Zhao; Wenjun Fan; Chao Yi; Hai-Xia Liu; Yulin Ding; Mingyuan Wang; Yan Wang; Shan Zhang; Xuewen Su; Yonghong Liu (Acta Parasitologica, 2025)

Effects of bicarbonate on antioxidant, immune, osmolytic and metabolic capabilities of Scylla paramamosain - Chenxi Che; Yuntao Li; Kangxiang Qin; Ziwei Fan; Wenjun Li; Shan Gao; Peng Yang; Chunlin Wang; Changkao Mu; Huan Wang (Aquaculture, 2025)

Association of residential greenness exposures on disability: Findings from the cohort study on global AGEing and Adult Health (SAGE) in China - Zhiqing Chen; Yan Shi; Yanfei Guo; Siwen Yu; Qijiong Zhu; Shangfeng Yang; Yuan Zheng; Yayi Li; Yixiang Huang; Wan Peng; Guanhao He; Jianxiong Hu; et al. (Environmental Research, 2025)

Competitive adsorption mechanisms of phosphorus species on montmorillonite-iron oxyhydroxide complexes - Chonghao Jia; Jialin Chi; Yuke Fan; Lihong Qin; Tao Ren; Christine V. Putnis; Wenjun Zhang (Chemical Geology, 2025)

Integrative transcriptomics and metabolomics analysis provide insight into the formation of skin pigmentation diversity in Chinese soft-shelled turtle (Pelodiscus sinensis) - Ming Qi; Wei Liu; Wei Li; Guangmei Chen; Wenrui Shi; Gaohua Yao; Yijiang Bei; Fan Yuan; Qinghui Meng; Fan Zhou; Wenjun Ma; Xueyan Ding; et al. (Aquaculture, 2024)

Ionic titanium is expected to improve the nutritional quality of Tartary buckwheat sprouts through flavonoids and amino acid metabolism - Hang Yuan; Qiang Wang; Jianxin Tan; Jingyu Wu; Chenggang Liang; Yan Wang; Tingting Deng; Zhiming Hu; Changying Liu; Xueling Ye; Qi Wu; Xiaoyong Wu; et al. (Food Chemistry, 2024)

Exceptional heatwaves and mortality in Europe: Greater impacts since the coronavirus disease 2019 outbreak - Zhiwei Li; Yinguang Fan; Zhiwei Xu; Hung Chak Ho; Shilu Tong; Cunrui Huang; Zhongliang Bai; Yiming Gai; Wenjun Cheng; Jihong Hu; Yufan Feng; Hao Zheng; et al. (Environmental Pollution, 2024)

First report of Giardia duodenalis in dairy cattle and beef cattle in Shanxi, China - Li Zhao; Yan Wang; Mingyuan Wang; Shan Zhang; Lifeng Wang; Zhansheng Zhang; Hailiang Chai; Chao Yi; Wenjun Fan; Yonghong Liu (Molecular Biology Reports, 2024)

Effect of antibiotic perturbation on nitrous oxide emissions: An in-depth analysis - Wenjun Yu; Kashif Hayat; Junwei Ma; Xiaoping Fan; Yuyi Yang; Zulin Zhang; Qiaogang Yu; Mingrong Qian; Hui Lin (Critical Reviews in Environmental Science and Technology, 2024)

A miniaturized microfluidic nanoplasmonic sensor with cavity reflection enhancement for ultrasensitive molecular interaction analysis - Hongli Fan; Mingqian Chen; Rui Li; Youqian Chen; Shaoqi Zeng; Wenjun Hu; Gang L. Liu; Chunmeng Sun; Liping Huang (Chemical Engineering Journal, 2024)

Exogenous microbubbles contribute to valorization of microalgal compounds by ultrasound-assisted extraction - Yong Deng; Lihua Fan; Wenjun Wang; Ruiling Lv; Donghong Liu (Bioresource Technology, 2024)

Aluminum substitution stabilizes organic matter in ferrihydrite transforming into hematite: A molecular analysis - Yuke Fan; Jialin Chi; Lijun Wang; Chonghao Jia; Wenjun Zhang (Science of The Total Environment, 2024)

Effects of the pesticide carbendazim on broiler chicken health and carbendazim residue levels in broiler tissues - Wanjun Zhang; Yutong Tang; Ruiqi Fan; Fude Zhang; Yongchen Li; Jianjun Zang; Wenjun Yang; Zongyi Wang; Xiaoyan Yuan; Yuan Yang; Yiqiang Chen (Veterinary Research Communications, 2024)

Chloroplast-mimicking nanoreactor for enhanced CO2 electrocatalysis - Weiguang Ma; Wenjun Fan; Qinye Li; Hefeng Zhang; Kaixin Zhu; Chenghua Sun; Lianzhou Wang; Xu Zong (Science Bulletin, 2024)

Defect-decorated Cu2MoS4 as a new efficient hydrogen evolution cocatalyst: Rich active sites, rapid charge transfer and optimized hydrogen adsorption - Mei Dong; Wenjun Li; Liang Geng; Xiaohui Ma; Yajie Li; Yueyan Fan; Ajmal Khan (Fuel, 2024)

Transcriptomic and physiological analysis provide new insight into seed shattering mechanism in Pennisetum alopecuroides ‘Liqiu’ - Yue Xu; Lingyun Liu; Ming Jia; Ke Teng; Na Mu; Yidi Guo; Muye Liu; Juying Wu; Wenjun Teng; Linkai Huang; Xifeng Fan; Yuesen Yue (Theoretical and Applied Genetics, 2024)

Profiling of fungal communities in functional food Cistanches herba using high–throughput sequencing - Chune Fan; Rong Xu; Mengyue Guo; Wenjun Jiang; Meihua Yang; Yujie Dao; Xiaohui Pang (Food Bioscience, 2024)

Enhancing thermal comfort prediction in high-speed trains through machine learning and physiological signals integration - Wenjun Zhou; Mingzhi Yang; Xiaoyan Yu; Yong Peng; Chaojie Fan; Diya Xu; Qiang Xiao (Journal of Thermal Biology, 2024)

LRRK2 is involved in heat exposure-induced acute lung injury and alveolar type II epithelial cell dysfunction - Yindan Wang; Wenjun Fan; Guoqing Zhang; Lisha Zhao; Ting Li; Lu Zhang; Tong Hou; Huihua Hong; Zhenqiang You; Qinghua Sun; Ran Li; Cuiqing Liu (Environmental Pollution, 2024)

Variations of the fungal microbiome in Corydalis Rhizoma with different collection areas, processing methods, and storage conditions - Wenjun Jiang; Mengyue Guo; Jingsheng Yu; Chune Fan; Meihua Yang; Xiaohui Pang (Food Research International, 2024)

Establishing rapid charge channel via synergism of oxygen vacancy and interfacial effect to promote stable photocatalytic NO purification - Wendong Zhang; Ailin Jiang; Wenjie He; Wenjun Ma; Yuerui Ma; Wangxing Ai; Xing'an Dong; Yi Wang; Peng Chen; Fan Dong (Chemical Engineering Journal, 2024)

Influence of sea-land breeze on the formation and dissipation of severe dense fog and its burst reinforcement in the Yellow Sea coastal area, China - Ya Gao; Duanyang Liu; Shuqi Yan; Wenjun Zhou; Hongbin Wang; Fan Zu; Qin Mei; Chuanxiang Yi; Ye Sheng (Science China Earth Sciences, 2024)

Thermal sensation prediction model for high-speed train occupants based on skin temperatures and skin wettedness - Wenjun Zhou; Mingzhi Yang; Yong Peng; Qiang Xiao; Chaojie Fan; Diya Xu (International Journal of Biometeorology, 2024)

Study on engineering geological characteristics of southwest shale oil based on nuclear magnetic resonance imbibition flooding technology - Liang Wang; Fan Yu; Jiqing Shi; Junliang Peng; Wenjun Zhao; Yuntao Liu; Jun Yan (Acta Geophysica, 2024)

Direct observations of nanoscale brushite dissolution by the concentration-dependent adsorption of phosphate or phytate - Xinfei Ge; Yuke Fan; Hang Zhai; Jialin Chi; Christine V. Putnis; Lijun Wang; Wenjun Zhang (Water Research, 2024)

Combining landscape patterns and ecosystem services to disclose ecosystem changes in tropical cropland-forest shifting zones: Inspiration from Mainland Southeast Asia - Feifei Fan; Wenjun Li; Zhiming Feng; Yanzheng Yang (Journal of Cleaner Production, 2024)

A SERS aptasensor based on a flexible substrate for interference-free detection of carbendazim in apple - Xiaoou Wei; Wenjun Song; Yushan Fan; Yue Sun; Zhihua Li; Shiqi Chen; Jiyong Shi; Di Zhang; Xiaobo Zou; Xuechao Xu (Food Chemistry, 2024)

Integrated metabolomic and transcriptomic analyses reveal the molecular mechanism of amino acid transport between source and sink during tea shoot development - Jie Zhang; Kangwei Sun; Yu Wang; Wenjun Qian; Litao Sun; Jiazhi Shen; Zhaotang Ding; Kai Fan (Plant Cell Reports, 2024)

Dynamics of the distribution of invasive alien plants (Asteraceae) in China under climate change - Wenjun Yang; Shuxia Sun; Naixian Wang; Peixian Fan; Chao You; Renqing Wang; Peiming Zheng; Hui Wang (Science of The Total Environment, 2023)

Anaerobic biodegradation of azo dye reactive black 5 by a novel strain Shewanella sp. SR1: Pathway and mechanisms - Jiale Liu; Lu Fan; Wenjun Yin; Shusheng Zhang; Xiaomei Su; Hongjun Lin; Haiying Yu; Zhenghai Jiang; Faqian Sun (Journal of Environmental Management, 2023)

Cold stress causes liver damage by inducing ferroptosis through the p38 MAPK/Drp1 pathway - Yujie Huang; Kun Xiong; Aiping Wang; Zejun Wang; Qi Cui; Hongchen Xie; Tian Yang; Xu Fan; Wenjun Jiang; Xiaoling Tan; Qingyuan Huang (Cryobiology, 2023)

Molecular mechanisms of phosphorus immobilization by nano-clay mediated by dissolved organic matter - Chonghao Jia; Yuke Fan; Jialin Chi; Christine V. Putnis; Chuanqin Huang; Wenjun Zhang (Chemical Geology, 2023)

Water distribution based on SAR and optical data to improve hazard mapping - Yang Han; Fan Deng; Jie Gong; Zhiyuan Li; Ziyang Liu; Jing Zhang; Wenjun Liu (Environmental Research, 2023)

The first complete mitochondrial genome of Carex (C. breviculmis): a significantly expanded genome with highly structural variations - Shenjian Xu; Ke Teng; Hui Zhang; Juying Wu; Liusheng Duan; Hongyu Zhang; Haifeng Wen; Wenjun Teng; Yuesen Yue; Xifeng Fan (Planta, 2023)

Nitrogen deposition weakens the stimulatory effect of Moso bamboo (Phyllostachys edulis) leaf litter on soil CO2 emissions - Shoujia Zhuo; Youchao Chen; Haikuo Zhang; Wenting Jiang; Bo Fan; Yongfu Li; Bing Yu; Wenjun Li; Min Duan; Scott X. Chang; Yanjiang Cai (Journal of Soils and Sediments, 2023)

Efficient photoelectrochemical aptasensing of di-2-ethylhexyl phthalate in environmental samples based on N, S co-doped graphene quantum dots/TiO2 nanorods - Dongyun Liao; Jinfeng Zhi; Qiang Wang; Wenjun Yan; Yujing Guo; Yujie Han; Chuan Dong; Yong Xiao; Hongcun Bai; Wenting Liang; Lifang Fan (Analytica Chimica Acta, 2023)

ROS-responsive hierarchical targeting vehicle-free nanodrugs for three-pronged Parkinson’s disease therapy - Zhongxiong Fan; Hao Jin; Xiaofeng Tan; Ying Li; Dao Shi; Qiuli Wang; Jiahao Meng; Wenjun Li; Caixia Chen; Lu Peng; Zhenqing Hou; Jingwen Li; et al. (Chemical Engineering Journal, 2023)

Assessment of five SMAP soil moisture products using ISMN ground-based measurements over varied environmental conditions - Chuanxiang Yi; Xiaojun Li; Jiangyuan Zeng; Lei Fan; Zhiqing Xie; Lun Gao; Zanpin Xing; Hongliang Ma; Antoine Boudah; Hongwei Zhou; Wenjun Zhou; Ye Sheng; et al. (Journal of Hydrology, 2023)

Comparative transcriptome analysis of non-germinated and germinated spores of Enterocytozoon hepatopenaei (EHP) in vitro - Yabin Dou; Leiting Zhang; Hui Shen; Sheng Zhang; Xiaohui Cao; Yi Qiao; Ge Jiang; Jie Cheng; Xihe Wan; Xianping Fan; Hui Li; Libao Wang; et al. (Journal of Invertebrate Pathology, 2023)

Design an efficient photoelectrochemical aptasensor for PCB72 based on CdTe@CdS core@shell quantum dots-decorated TiO2 nanotubes - Dongyun Liao; Guifang Liang; Yuyao Liu; Wenjun Yan; Yujing Guo; Wenting Liang; Chuan Dong; Lifang Fan (Journal of Hazardous Materials, 2023)

Comparative Transcriptome and Hormone Analysis of Mature Leaves and New Shoots in Tea Cuttings (Camellia sinensis) among Three Cultivars with Different Rooting Abilities - Kai Fan; Yujie Shi; Danni Luo; Wenjun Qian; Jiazhi Shen; Shibo Ding; Zhaotang Ding; Yu Wang (Journal of Plant Growth Regulation, 2022)

Retention of soil organic matter by occlusion within soil minerals - Jialin Chi; Yuke Fan; Lijun Wang; Christine V. Putnis; Wenjun Zhang (Reviews in Environmental Science and Bio/Technology, 2022)

Altered albedo dominates the radiative forcing changes in a subtropical forest following an extreme snow event - Palingamoorthy Gnanamoorthy; Qinghai Song; Junbin Zhao; Yiping Zhang; Yuntong Liu; Wenjun Zhou; Liqing Sha; Zexin Fan; Pramit Kumar Deb Burman (Global Change Biology, 2021)
Subtropical forests are important ecosystems globally due to their extensive role in carbon sequestration. Extreme climate events are known to introduce disturbances in the ecosystem that cause long‐term changes in carbon balance and radiation reflectance. However, how these ecosystem function changes contribute to global warming in terms of radiative forcing (RF), especially in the years following a disturbance, still needs to be investigated. We studied an extreme snow event that occurred in a subtropical evergreen broadleaved forest in south‐western China in 2015 and used 9 years (2011–2019) of net ecosystem CO 2 exchange (NEE) and surface albedo ( α ) data to investigate the effect of the event on the ecosystem RF changes. In the year of the disturbance, leaf area index (LAI) declined by 40% and α by 32%. The annual NEE was −718 ± 128 g C m −2 as a sink in the pre‐disturbance years (2011–2014), but after the event, the sink strength dropped significantly by 76% (2015). Both the vegetation, indicated by LAI, and α recovered to pre‐disturbance levels in the fourth post‐disturbance year (2018). However, the NEE recovery lagged and occurred a year later in 2019, suggesting a more severe and lasting impact on the ecosystem carbon balance. Overall, the extreme event caused a positive (warming effect) net RF which was predominantly caused by changes in α (90%–93%) rather than those in NEE. This result suggests that, compared to the climate effect caused by forest carbon sequestration changes, the climate effect of α alterations can be more sensitive to vegetation damage induced by natural disturbances. Moreover, this study demonstrates the important role of vegetation recovery in driving canopy reflectance and ecosystem carbon balance during the post‐disturbance period, which determines the ecosystem feedbacks to the climate change.

Biosynthesis and preparation of phycoerythrobilin in recombinant Escherichia coli - Wenjun Li; Chengbo Ma; Baosheng Ge; Fan Zang; Song Qin; Jian Lin (Journal of Applied Phycology, 2021)

The effect of polyvinyl alcohol solution with a high degree of alcoholysis on the expansion and cracking behaviour of quicklime-treated soil in earthen sites - Qiyong Zhang; Wenwu Chen; Wenjun Fan; Duanwu Liu (Bulletin of Engineering Geology and the Environment, 2021)

Nucleoprotein phosphorylation site (Y385) mutation confers temperature sensitivity to influenza A virus due to impaired nucleoprotein oligomerization at a lower temperature - Weinan Zheng; Liang Cui; Minghui Li; Yun Li; Wenhui Fan; Limin Yang; Jing Li; Lei Sun; Wenjun Liu (Science China Life Sciences, 2021)

Preparation of high-purity R-phycoerythrin and R-phycocyanin from Pyropia yezoensis in membrane chromatography - Fan Zang; Song Qin; Chengbo Ma; Wenjun Li; Jian Lin (Journal of Applied Phycology, 2020)

Aging exacerbates impairments of cerebral blood flow autoregulation and cognition in diabetic rats - Shaoxun Wang; Wenshan Lv; Huawei Zhang; Yedan Liu; Longyang Li; Joshua R. Jefferson; Ya Guo; Man Li; Wenjun Gao; Xing Fang; Ian A. Paul; Grazyna Rajkowska; et al. (GeroScience, 2020)

In vitro induction and characterization of hexaploid Pennisetum × advena, an ornamental grass - Yuesen Yue; Xifeng Fan; Yaofang Hu; Chao Han; Hui Li; Wenjun Teng; Hui Zhang; Ke Teng; Haifeng Wen; Xuejun Yang; Juying Wu (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Observation and analysis of VOCs in nine prefecture-level cities of Sichuan Province, China - Wenjun Wang; Tingting Xiong; Wei Zhang; Bin Luo; Dongmei Wang; Xincheng Jiang; Zhihan Rao; Yan Jiang; Yue Liu; Huan Cheng; Xiaojing Luo; Meikun Fan; et al. (Environmental Monitoring and Assessment, 2020)

NBS-LRR gene family in banana (Musa acuminata): genome-wide identification and responses to Fusarium oxysporum f. sp. cubense race 1 and tropical race 4 - Wenjun Chang; Heng Li; Hanqing Chen; Fan Qiao; Huicai Zeng (European Journal of Plant Pathology, 2020)

Nanopore sequencing of African swine fever virus - Lijia Jia; Mengwei Jiang; Ke Wu; Juefu Hu; Yang Wang; Weipeng Quan; Mengchan Hao; Haizhou Liu; Hongping Wei; Wenhui Fan; Wenjun Liu; Rongliang Hu; et al. (Science China Life Sciences, 2020)

Compound C attenuates NLRP3 inflammasome despite AMPK knockdown in LPS plus palmitate-induced THP-1 cells - Yuxing Liu; Honghui He; Liangliang Fan; Jingjing Yuan; Hao Huang; Wenjun Yang; Linghao Wang; Zhaohui Mo; Fang Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Prevalence of shrimp microsporidian parasite Enterocytozoon hepatopenaei in Jiangsu Province, China - Hui Shen; Yi Qiao; Xihe Wan; Ge Jiang; Xianping Fan; Hui Li; Wenjun Shi; Libao Wang; Xiaoran Zhen (Aquaculture International, 2019)

Landscape structure and network characteristics of the greenway system in Guangzhou City, South China - Sangsang Fan; Xiuzhi Chen; Hai Ren; Wenjun Shen; Rongbo Xiao; Qianmei Zhang; Zhifeng Wu; Yongxian Su (Landscape and Ecological Engineering, 2019)

Synaptobrevin-2 facilitates the trafficking and function of atrial SK2 channel - Tao Li; Xuehui Fan; Yiyan Yu; Linlin Chen; Wenjun Huang; Yan Yang; Jimin Cao; Xiaorong Zeng; Xiaoqiu Tan (Science China Life Sciences, 2018)

A genetic variant in COL11A1 is functionally associated with lumbar disc herniation in Chinese population - Wenjun Liu; Guisen Sun; Longsheng Guo; Lulu Wang; Weiqiang Fan; Minglei Lang; Dan Chen; Xinhao Yi (Journal of Genetics, 2017)

Change of the N-terminal codon bias combined with tRNA supplementation outperforms the selected fusion tags for production of human d-amino acid oxidase as active inclusion bodies - Weiyu Wang; Jiaqi Sun; Wenjun Xiao; Li Jiang; Ruyue Wang; Jun Fan (Biotechnology Letters, 2017)

Identification of up-regulated genes provides integrated insight into salt-induced tolerance mechanisms in Sesuvium portulacastrum roots - Wei Fan; Wenjun Chang; Xiwen Liu; Chuan Xiao; Jianli Yang; Zhili Zhang (Acta Physiologiae Plantarum, 2017)

An aquaporin gene from halophyte Sesuvium portulacastrum, SpAQP1, increases salt tolerance in transgenic tobacco - Wenjun Chang; Xiwen Liu; Jiahong Zhu; Wei Fan; Zhili Zhang (Plant Cell Reports, 2016)

Impacts of Nomad Sedentarization on Social and Ecological Systems at Multiple Scales in Xinjiang Uyghur Autonomous Region, China - Mingming Fan; Wenjun Li; Chengcheng Zhang; Lanhai Li (Ambio, 2014)